Cerests as knowledge builders in the COVID-19 pandemic: analysis of actions carried out in the state of São Paulo/Brazil - Jorge, Carlos Francisco Bitencourt [UNESP]; Veríssimo, Daniela Maria Maia; Cazane, Ana Lívia [UNESP]; Ribeiro, Karla Cristina Rocha; Menegassi, Cláudia Herrero Martins (My University, 2023)
The objective of this article is to report the experiences, actions and knowledge construction of the Healthcare Reference Centers of Workers (in Portuguese Cerests) inserted in the State of São Paulo during the period of the COVID-19 pandemic. It is important to note that the Cerests are inserted in a National Network of Comprehensive Health Care for Workers (in Portuguese Renast). Thus, a survey was carried out among the Cerests who have a site, blog or social networks and, with it, the sequential explanatory method was used, the information collected, systematized and analyzed on the knowledge built and their actions carried out in education, vigilance and assistance. The results obtained are analyzed in light of the available literature that deals with the construction of knowledge, the health of the worker and on the actions carried out in the State of São Paulo in the face of the COVID-19 pandemic. The work was concluded with important reflections on the importance of the knowledge built within a summary of the actions identified by the Cerests, thus observing that most of them follow educational guidelines and are marked by knowledge. This summary demonstrates the ingredients built during the pandemic period, these being guides for the other Cerests in the face of the pandemic, and used in the post-pandemic process.
Cerests como constructores de conocimiento en la pandemia de COVID-19: análisis de acciones realizadas en el Estado de São Paulo/Brasil
Os Cerests como construtores de conhecimentos na pandemia de COVID-19: análise das ações realizadas no estado de São Paulo/Brasil
Keywords: Cerests; COVID-19; Knowledge; Renast; Sao Paulo; worker's health